Asymptotic stability of planar rarefaction wave to 3D radiative hydrodynamics. (April 2019) - Huang, Bingkang; Zhang, Lan
Abstract: We are concerned with the large-time behavior of the planar rarefaction wave for the 3d radiative hydrodynamics. We show the nonlinear stability of the planar rarefaction wave in two cases. For the one, the viscosity coefficient μ and transport coefficient κ are positive constant and the proof is motivated by Li et al. (2018). For another, we neglect the transport coefficient κ . It is crucial to use the symmetrization of quasi-linear form of the perturbation system (4.42).